Understanding the Severity of Alcohol as a Risk Factor for High Blood Pressure in the Presence of Social and Epidemiological Variables: A South African Cross Sectional Study - Ramzi, Abby (Université d'Ottawa / University of Ottawa, 2016)
Background: the incidence of high blood pressure in South Africa has increased over the past few decades (Chopra et al., 2009; Seedat, 2012). Public health scientists have warned that this trend might be correlated to a multitude of unhealthy behaviors at the individual level, including heavy alcohol consumption (Chopra et al., 2009; Hillbom et al., 2011; Seedat, 2012; Strogatz et al., 1991). Previous studies have established a synergistic effect between alcohol consumption and high blood pressure leading to an increased risk of cardiovascular and renal disease within countries of the global north (Abe et al., 1994; Keil et al., 1993; Steyn et al., 1997). Not only is this trend under studied in South Africa, the severity of alcohol’s impact on blood pressure remains to be discerned in the country. Objectives: shedding light on the epidemiological and social factors impacting the association between alcohol consumption and blood pressure. Based on previous observations, it is hypothesized that certain epidemiological factors will be strongly associated with high blood pressure in the presence of alcohol consumption. Findings from this research would inform healthcare professionals on the diagnosis of high blood pressure cases in the South African population as this research aims to identify the factors associated with high blood pressure, thus, alleviating the problem of underdiagnosed cases that have been found to incur heavy costs on the healthcare system (Chopra et al., 2009; Seedat, 2012). Methods: in the present study, we have investigated social and epidemiological factors, as informed by previous research, which are associated with blood pressure in the presence of alcohol consumption within a South African context by using data collected from the South African Demographic and Health Survey (SADHS). Conclusion: Our findings indicate a correlation between ethnicity and blood pressure, as well as having a heart attack and high blood pressure measurements.
Keywords: South Africa; Alcohol; Blood pressure